Antibacterial activity and minimum inhibitory concentration of ethanolic leaf extract of clinacanthus nutans - Suwandi, Rosdiana; Kahar, Qhairunnisaa; Hashim, Nur’alin Syahmina; Abdul Latip, Normala; Mohamad, Mashani (Faculty of Pharmacy, 2025)
Herbal medicine with antimicrobial properties has the potential to serve as an alternative therapeutic option to modern pharmaceuticals. Clinacanthus nutans (C. nutans), a medicinal plant widely distributed across South East Asia, is known to possess a diverse range of bioactive compounds that give significant antioxidant, anti-inflammatory, anti-proliferative and antibacterial properties. Previous research has primarily investigated the antibacterial properties of C. nutans using water and methanol extractions. However, studies on ethanol extracts have been limited. Therefore, this study aimed to evaluate the antibacterial properties and minimum inhibitory concentration of ethanolic leaves extract of C. nutans against Gram-positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative (Escherichia coli and Pseudomonas aeruginosa) bacteria. The methodology involved ethanol extraction of C. nutans leaves, followed by antibacterial evaluations via disk diffusion test, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) methods. The yield obtained from the ethanol extraction was 7.1%. Results from the antibacterial evaluations showed that the extract was able to inhibit the growth of all tested bacteria, with the highest zone of inhibition against S. aureus (11.0 ± 0.6 mm) and the lowest against E. coli (6.5 ± 0.5 mm) at concentration of 500 mg/ml. The MIC and MBC values further confirmed this activity, with the extract showing a notable lower MIC/MBC for S. aureus (15.63/15.63 mg/ml) compared to E. coli (62.5/250 mg/ml). As a conclusion, the ethanolic extract of C. nutans has demonstrated antibacterial activity against all tested bacterial strains, including both Gram-positive and Gram-negative species. These findings support the potential of leaves of this plant to be used as a broad-spectrum natural antimicrobial agent for future therapeutic applications.